Tekstil Indonesia vs Tiongkok: Peluang Ekspor dan Ancaman Produk Impor Murah - Eriza Selviani; Daspar (Indo Publishing, 2025)
The textile industry is one of the important sectors in the Indonesian economy, it plays a significant role in job creation and the country's export contribution. However, the dynamics of global trade, especially trade relations with China, present several challenges. The purpose of this article is to critically analyze the prospects of Indonesian textile exports to the international market and the risks posed by the spread of cheap textile products from China to the domestic market. A qualitative approach using secondary data from trade reports and industrial policies is used to find that the Indonesian textile industry still faces significant problems in terms of price, quality, and production efficiency. Although there are great opportunities to expand exports, especially to non-traditional countries. In addition, one of the problems that must be fixed immediately is our dependence on imported raw materials from China. Consequently, to increase the competitiveness of the national textile industry, a comprehensive plan is needed that includes the development of new technologies, market diversification, and protection of domestic industries.